Complete Advanced: Students Book with Answers - Brook-Hart G.; Haines Simon (Cambridge Cambridge University Press, 2014)
Complete Advanced provides thorough preparation for the revised 2015 Cambridge English: Advanced (CAE) exam. This pack consists of the Students Book with answers with CD-ROM and Class Audio CDs. The Students Book fully prepares students to tackle each part of every exam paper. Unique grammar and vocabulary exercises train students to avoid common mistakes. The interactive CD-ROM provides comprehensive extra practice of the language and topics covered in the book and supports mixed ability focusing on students own particular areas of difficulty. The Class Audio CDs contain the recordings for the listening exercises in the Students Book. A full practice test is available online for teachers to access.
Keywords: 811.111